Evaluation of Writing Skills (Imla) of Grade 2 KMI Students at Pondok Modern El-Haq Jombang: تقييم مهارة الكتابة (الإملاء) لدى طلاب الصف الثاني في معهد الحق للتربية الإسلامية الحديثة بجومبانج - Wahyudin, Abdullah Abas; Abd. Faishol; Muhammad Nanang Qosim (Institut Muslim Cendekia, 2025)
This study aims to evaluate the actual performance of second-grade students of Madrasah Mu'allimin Islamiyah (KMI) at El Haq Modern Islamic Boarding School Jombang in writing skills (imla') and analyze their most frequent spelling errors. The researcher employed the descriptive analytical method, relying on a standardized dictation test as the main data collection instrument from a sample of (48) students selected randomly. The findings indicate that the mean score of the students' performance was (63.75), categorizing their general achievement level as